An Example of Translation Criticism considering Skopos Theory: Adaptation of W. Shakespeare’s A Midsummer Night’s Dream into a Children’s Theatre Play Bir Yaz Masalı - Yeşim Pirpir Avan; Lale Özcan (İstanbul Üniversitesi Çeviribilim Dergisi)
Children’s theatre translation can be defined as the translation/adaptation of theatre plays written for adults or children in the source language for children in the target language. This study includes Bir Yaz Masalı, a children’s theatre play, adapted from A Midsummer Night’s Dream by Shakespeare, the preface written by the translator to the book of the play (2021), and an online translator interview. The play is analysed in accordance with the steps of translation criticism built considering Skopos theory by Hans J. Vermeer and applied by Tellioğlu in her master’s thesis. (Tellioğlu, 1996). As a result of the analysis, it is concluded that a theatre practitioner and translator, Emel Bala, establishes relatively short and plain sentences in a nondidactic way and creates musical and poetic language via Turkish proverbs, idioms, rhymes, and lyrics, paying attention to the principles “suitability for children” and “children’s reality” (Şirin, 2016, p. 24). It is significant that translators translate or adapt a theatre play for children in light of children’s developmental features, language development, inner world and expectations. We put forward that this article will contribute to the field of children’s theatre translation, which is unexplored, and inspire further research in the field.